Factors affecting the esterification of lauric acid using an immobilized biocatalyst: enzyme characterization and studies in a well-mixed reactor - Vazquez-Lima, F.; Pyle, D. L.; Asenjo, J.A. (John Wiley & Sons, Inc., 2010)
The esterification of lauric acid with geraniol catalyzed by the commercially immobilized lipase preparation from Mucor miehei, Lipozyme(®), was studied in well-stirred flasks. The enzyme support was characterized in terms of its internal and external surface area, protein location, and protein content. It was found that the enzyme was mainly located on the external surface of the support, therefore, internal diffusional limitations were not important. It was also shown that the protein content of the support depends on the size of the particle, with smaller particles containing higher amounts of protein per unit weight. Under the conditions studied, the reaction was not under external mass transfer limitations, and the initial reaction rate depended on the size of the support particles. This was mainly due to the different protein contents on the support as a function of particle size and not to internal or external mass transfer limitations. Also, it was found that the inhibition exerted by water was predominantly a physical effect due to its accumulation around the enzyme. It was also found that the reaction was substrate inhibited by lauric acid, but not by geraniol.